Why So Silent? The Supreme Court and the Second Amendment Debate After DC v. Heller - Emma Long (European Journal of American Studies)
In District of Columbia v. Heller (2008) the Supreme Court appeared to give to gun rights activists what they had campaigned for since the 1970s: a ruling that the Second Amendment encompassed an individual right to bear arms for the purposes of self-defence.  But as the debate about gun rights returned to the top of the political agenda in the United States as a result of a series of high profile mass shootings in 2015 and the death of Justice Antonin Scalia in 2016, two things became clear: that Heller had not ended the political or legal debate about Second Amendment rights and that the Supreme Court had been noticeably absent from the debate since applying the Heller ruling to the states in McDonald v. Chicago in 2010.  This article argues that, far from the success claimed by gun rights supporters, the consequences of Heller fundamentally undermined some of their key arguments and forced a shift in the nature of the debate.  Both worked to keep the Supreme Court away from the debate at a time when greater clarity about the meaning of Heller was needed.